Comprehensive analysis of clinical outcomes, infectious complications and microbiological data in newly diagnosed multiple myeloma patients: a retrospective observational study of 92 subjects - Desantis, Vanessa; Borrelli, Paola; Panebianco, Teresa; Fusillo, Antonio; Bochicchio, Donatello; Solito, Angelo; Pappagallo, Fabrizio; Mascolo, Antonella; Ancona, Anna; Cicco, Sebastiano; Cerchione, Claudio; Romano, Alessandra; et al. (Clinical and experimental medicine, 2024)
Patients with multiple myeloma (MM) have an increased risk of sepsis due to underlying disease- and treatment-related immunosuppression. However, data on sepsis incidence, causative pathogens, and impact on outcomes in newly diagnosed MM (NDMM) are limited. We conducted a retrospective observational study of 92 NDMM patients who developed sepsis between 2022 and 2023 at a tertiary care center in Italy. Patient characteristics, sepsis criteria [Quick Sequential Organ Failure Assessment, Systemic Inflammatory Response Syndrome (SIRS)], microbiology results, and associations with progression-free survival (PFS) were analyzed. In this cohort of 92 critically-ill patients, pathogenic organisms were identified via microbiological culture in 74 cases. However, among the remaining 18 culture-negative patients, 9 exhibited a SIRS score of 2 and another 9 had a SIRS score of 4, suggestive of a clinical presentation consistent with sepsis despite negative cultures. Common comorbidities included renal failure (60%), anemia (71%), and bone disease (83%). Gram-negative (28%) and Gram-positive (23%) bacteria were frequent causative organisms, along with fungi (20%). Cox Univariate analyses for PFS showed statically significant HR in patients with albumin ≥ 3.5 vs < 3.5 (HR = 5.04, p < 0.001), Karnofsky performance status ≥ 80 vs < 80 (HR = 2.01, p = 0.002), and early-stage vs late-stage disease by International Staging System (HR = 4.76 and HR = 12.52, both p < 0.001) and Revised International Staging System (R-ISS III vs R-ISS I, HR = 7.38, p < 0.001). Sepsis is common in NDMM and associated with poor outcomes. Risk stratification incorporating sepsis severity, comorbidities, and disease stage may help guide preventive strategies and optimize MM management.